Constructed wetland system for treating wastewater of scattered small industries: A case study of fermented fish production industry in Phayao City, Thailand - Perera R. (2014)
In the absence of centralised treatment systems and collection networks, wastewater discharged by small industries often end up in surface waterbodies. When those industries are scattered in a wider area, decentralised systems are also not effective in solving the problem. This paper presents the results of a community-based project that was implemented to demonstrate how wastewater problem of scattered small industries can be addressed. The paper presents the application of 'constructed wetland' technology to treat wastewater discharged by home-based industries specialised in fermented fish production. It shows that constructed wetland technology can efficiently resolve the wastewater problem of fermented fish production industry. However, stakeholder participation and logistical arrangements are found to be key issues that determine the effectiveness of this technology to address the wastewater problem of scattered industrial units. Copyright © 2011 Inderscience Enterprises Ltd.